Market entry for wind energy: Strategic approaches for the original equipment manufacturer. Issue 3 (13th October 2021) - Zwarteveen, Jan Willem; Zawwar, Imran; Angus, Andrew
Abstract: Wind energy is a valuable resource, but many developing and emerging economies (DEEs) are not utilizing the tremendous wind capacity available to them. This means there is a potential for wind turbine original equipment manufacturers (OEMs) to penetrate new markets to increase profits, and to contribute to Sustainable Development Goals. This article explores the potential triggers for wind energy diffusion and provides the basis for inclusive market entry strategies for wind power OEMs. Indications are that early wind energy path creation is driven by climate adaptation, vested interests in fossil fuels and hydropower, and the business case potential. A negative business case potential in many DEEs formed a substantial barrier. A shift to increased local value creation, collaboration with traditional power producers, and promoting wind for climate adaptation are key novel inclusive market entry strategies to open and develop new markets.